Involutionary Processes in the Skeleton of Mediaeval and Contemporary Populations on the Basis of the Second Metacarpal - Rewekant, Artur (Anthropological Review, 1996)
The purpose of this paper is to present general trends in bone involution using second metacarpal in a mediaeval population and to compare the obtained results with data for contemporary groups. The findings may be valuable for the knowledge of general and regional human skeletal ageing.